2015
DOI: 10.1021/acsnano.5b03690
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Chemical Properties of Donor, Acceptor Centers in Graphene

Abstract: Chemical doping is one of the most suitable ways of tuning the electronic properties of graphene and a promising candidate for a band gap opening. In this work we report a reliable and tunable method for preparation of high-quality boron and nitrogen co-doped graphene on silicon carbide substrate. We combine experimental (dAFM, STM, XPS, NEXAFS) and theoretical (total energy DFT and simulated STM) studies to analyze the structural, chemical, and electronic properties of the single-atom substitutional dopants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…We should note that Telychko et al found the reverse relationship [24]; however their experiments employed a silicon carbide surface instead of the metallic surfaces presented in this paper. We theoretically investigated the effect of the substrate.…”
Section: Referencementioning
confidence: 57%
See 3 more Smart Citations
“…We should note that Telychko et al found the reverse relationship [24]; however their experiments employed a silicon carbide surface instead of the metallic surfaces presented in this paper. We theoretically investigated the effect of the substrate.…”
Section: Referencementioning
confidence: 57%
“…This effect is not localized on a single atom. This is attributed to the influence of the partially charged N atom on the charge density of the atoms to which it is bound [24]. At the location of the dopant atom there is also some contrast in the z min map.…”
Section: Referencementioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work [10] we demonstrated by scanning tunneling microscopy (STM) that, using a suitable doping procedure, the B dopants are homogeneously distributed in the graphene layer. However, STM experiments do not provide any information on their chemical states in terms of local bonding, their activation, and whether the doping procedure itself influences the substrate underneath the graphene layer.…”
mentioning
confidence: 99%